(untitled) (Research, Society and Development, 2020)
This study aimed to determine the chemical constituents, toxicity, antioxidant potential and larvicidal activity of the essential oil of Aniba rosaeodora Ducke against larvae of Aedes aegypti. The essential oil (EO) was extracted by hydrodistillation at 100 ° C for 3h. The physicochemical parameters were determined and the chemical composition was obtained by Gas Chromatography coupled to Mass Spectrometry (GC / MS). Toxicity was performed through the bioassay of Artemia salina Leach. The ABTS and DPPH assays were used to evaluate antioxidant activity and larvicidal activity was submitted to larvae of Aedes aegypti to EO solutions at concentrations of 10-100 mgL-1, where the mortality of larvae was evaluated and LC50 was determined using the Reed Muech method. The main chemical constituent found in the EO of A. rosaeodora was β-linalool 63.16%, being considered great promising for pharmaceutical synthesis. In the toxicity assay, LC50 ranged from 582 mg L-1 to 282 mgL-1and was classified as non-toxic. The EO showed larvicidal activity with LC50 of 41.07 mgL-1 and relevant antioxidant activity. According to the results found, it was possible to evaluate that the OE analyzed is composed of substances that have a good larvicidal effect compared to Aedes aegypti, thus encouraging its application potential.